IMPLEMENTATION OF GOVERNMENT EMPLOYEE SCHEME POLICIES WITH WORK AGREEMENTS IN DEALING WITH THE FISCAL LIMITATIONS OF THE BAUBAU CITY REGIONAL GOVERNMENT (NETWORK GOVERNANCE STUDY) - Asmiddin; Andi Tenri; Murtiani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the implementation of the policy of Government Employees with Work Agreements (PPPK) in the Baubau City Regional Government in facing fiscal limitations, using a network governance perspective. The PPPK policy is designed to strengthen the human resources of the state civil apparatus, but its implementation is faced with significant regional fiscal constraints. The descriptive-analytical qualitative research method is used to analyze the roles, authority, commitments, and synergy of actors in the policy network. The findings show that although each agency such as BKPSDM and BPKAD has carried out its functions according to its authority, there is a strong inter-actor dependence in aligning the needs of formation with budget capabilities. Authority is relational and distributed, influenced by fiscal considerations, shifting the paradigm from hierarchical bureaucracy to shared governance. The commitment of actors to the PPPK policy is relatively strong because it is considered a solution to fulfill human resources, but it is conditional on fiscal capacity and coordination quality. The synergy established through cross-agency coordination has succeeded in harmonizing needs and budgets, but is still dominated by administrative approaches and fiscal control, and has not fully achieved the ideal innovative strategic collaboration within the framework of network governance. The implication is that the success of PPPK policies in regions with fiscal limitations is highly dependent on the transformation of administrative synergy into adaptive and strategic collaboration, supported by strong network leadership.